2011
DOI: 10.1093/bioinformatics/btr708
|View full text |Cite
|
Sign up to set email alerts
|

ART: a next-generation sequencing read simulator

Abstract: Both source and binary software packages are available at http://www.niehs.nih.gov/research/resources/software/art.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1,308
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,379 publications
(1,313 citation statements)
references
References 8 publications
2
1,308
0
3
Order By: Relevance
“…To investigate the extent of this issue, we performed read simulation studies (Huang et al 2012) which showed that most paralogs are accurately mappable, and we excluded from further analysis those genes that are not mappable (see Supplemental Methods; Supplemental Fig. S7).…”
Section: Evolution Of H3k27me3 Is More Rapid In Gene Duplicatesmentioning
confidence: 99%
“…To investigate the extent of this issue, we performed read simulation studies (Huang et al 2012) which showed that most paralogs are accurately mappable, and we excluded from further analysis those genes that are not mappable (see Supplemental Methods; Supplemental Fig. S7).…”
Section: Evolution Of H3k27me3 Is More Rapid In Gene Duplicatesmentioning
confidence: 99%
“…The generated k genomes were saved in a FASTA format file named k-ploid.fa. Second, we used ART (Huang et al, 2012), a next-generation sequencing read simulator, to generate simulated reads from the the k genomes.…”
Section: Results On Simulated Datamentioning
confidence: 99%
“…To demonstrate that sequence data can be simulated without empirical data in hand, for this case study the sequencing error rate was drawn from the defaults provided with ART. Reads were simulated at an average coverage of 40 reads per site [13].…”
Section: Resultsmentioning
confidence: 99%
“…A user-specified tip will consist of the input anchor genome without any mutations. Using these simulated genomes, TreeToReads calls the read simulation software, ART, [13] to generate Illumina MiSeq paired-end reads. The user can apply a default sequence error model, or use the configuration file to specify an error model generated for observed data.…”
Section: Methodsmentioning
confidence: 99%